The Choquard Equation with Weighted Terms and Sobolev-Hardy Exponent - Yanbin Sang; Xiaorong Luo; Yongqing Wang (Journal of Function Spaces)
We study a nonlinear Choquard equation with weighted terms and critical Sobolev-Hardy exponent. We apply variational methods and Lusternik-Schnirelmann category to prove the multiple positive solutions for this problem.